2020
DOI: 10.1016/j.jhep.2020.05.023
|View full text |Cite
|
Sign up to set email alerts
|

An international multicenter study of protocols for liver transplantation during a pandemic: A case for quadripartite equipoise

Abstract: There is an urgent need for ethical frameworks to balance the need for liver transplantation against the availability of national resources during the COVID-19 pandemic. We describe a fourdimensional model of quadripartite equipoise that models these ethical tensions and can guide the regulation of transplant activity in response to the increasing burden on healthcare systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“… 66 We encourage LT centres to develop and improve local and global risk stratification pathways for LT donors and recipients, incorporating a combination of clinical history, chest radiology, and SARS-CoV-2 testing, 67 as well as ethical considerations regarding transplantation activities and allocation. 68 Measures should be taken to reduce the risk of SARS-CoV-2 infection in the peri-transplantation period. In areas of high disease burden, a COVID-19 free pathway through transplantation should be implemented, including strict social isolation for waiting list patients, telephone screening for symptoms and exposures before admission, and perioperative management in a designated clean intensive care unit and post-LT ward.…”
Section: Recommendations For the Management Of Patients With Chronic mentioning
confidence: 99%
See 1 more Smart Citation
“… 66 We encourage LT centres to develop and improve local and global risk stratification pathways for LT donors and recipients, incorporating a combination of clinical history, chest radiology, and SARS-CoV-2 testing, 67 as well as ethical considerations regarding transplantation activities and allocation. 68 Measures should be taken to reduce the risk of SARS-CoV-2 infection in the peri-transplantation period. In areas of high disease burden, a COVID-19 free pathway through transplantation should be implemented, including strict social isolation for waiting list patients, telephone screening for symptoms and exposures before admission, and perioperative management in a designated clean intensive care unit and post-LT ward.…”
Section: Recommendations For the Management Of Patients With Chronic mentioning
confidence: 99%
“…We encourage LT centres to develop and improve local and global risk stratification pathways for LT donors and recipients, incorporating a combination of clinical history, chest radiology, and SARS-CoV-2 testing, 67 as well as ethical considerations regarding transplantation activities and allocation. 68 …”
Section: Recommendations For the Management Of Patients With Chronic mentioning
confidence: 99%
“…Seventeen liver transplant centers from different countries participated in an international multi-center open survey, and [96] concluded that the majority of the centers adopted a “sickest first” strategy, otherwise a case by case is discussed. Almost all centers advised for COVID-19 screening for donor and recipient.…”
Section: Liver Transplantation and Covid-19mentioning
confidence: 99%
“…Cada centro debe valorar la situación epidemiológica, los recursos con los que cuenta (materiales y humanos) y el riesgo, tanto del donante como del receptor, así como del personal de salud, cuando se decida proceder o no con la realización del trasplante. 53 Si bien los modelos de manejo alrededor del mundo varían, los programas más importantes del mundo describieron y adoptaron un abordaje escalonado en la disminución de sus actividades. 41 Muchos países iniciaron con una disminución progresiva y gradual que se ajustó al avance de la pandemia en su región.…”
Section: Impacto Del Covid-19/sars-cov-2 En Los Programas De Trasplanunclassified